State-Dependent and Trait-Like Characteristics of Dysfunctional Attitudes in Patients With Major Depressive Disorder - Liu, Bangshan; Sun, Jinrong; Qin, Xuemei; Wang, Mi; Lu, Xiaowen; Dong, Qiangli; Zhang, Liang; Liu, Jin; Ju, Yumeng; Wan, Ping; Guo, Hua; Zhao, Futao; et al. (Frontiers in Psychiatry, 2020)
Background Studies have shown that patients with major depressive disorder (MDD) exhibit elevated dysfunctional attitudes (DAs). However, it remains controversial whether the DAs are state-dependent or trait-like features of MDD. Methods This study recruited 172 patients and 159 healthy controls (HCs) at baseline. DAs were respectively assessed by the 24-item Hamilton Depression Rating Scale (HAMD24) and the Chinese version of Dysfunctional Attitude Scale form A (C-DAS-A). After baseline, patients received a 6-month antidepressant treatment. General linear models were used to analyze the differences in the C-DAS-A total and factor scores between the acute and remitted MDD groups and the HC group. Paired t tests were used to assess the changes of C-DAS-A total and factor scores in the remitted MDD group before and after treatment. Results At baseline, patients with MDD showed significantly higher scores in C-DAS-A and its subscales than HCs (all P < 0.05). After treatment, the C-DAS-A total and factor scores decreased significantly in the remitted MDD group (all P < 0.05). However, the C-DAS-A total (P = 0.005) and five factors’ scores (vulnerability, attraction and repulsion, perfectionism, compulsion, and dependence) remained elevated in the remitted MDD group as compared with HCs (all P < 0.05). There were moderate correlations between the baseline and remission phase C-DAS-A total and five factors’ scores (all P < 0.05). Conclusion DAs show a mixture of state-dependent and trait-like characteristics in MDD with partial improvement in the remission phase. Special attention should be paid to the residual DAs in the remitted MDD for the prevention of relapse.